Enhanced antitumor effect of targeted nanoliposomal bleomycin. (15th June 2017) - Chiani, Mohsen; Azadmanesh, Kayhan; Shokrgozar, Mohammad Ali; Mehrabi, Mohammad Reza; Akbarzadeh, Azim; Norouzian, Dariush
Abstract : Folate receptor (FR)‐mediated drug delivery is a promising approach for active targeting of drugs to the FR‐positive tumor cells. Bleomycin (BLM) is an antitumor antibiotic with poor therapeutic activity as a result of its limited diffusion into tumor cells. The aim of this study was to investigate whether FR‐targeted PEGylated nanoliposomes (FPNL) can effectively deliver BLM to tumor cells and enhance its in vitro and in vivo efficacy. FPNL and PNL (non‐targeted) were prepared by thin film hydration method, and their physiochemical properties, cellular uptake, tissue distribution and tumor inhibitory effects were investigated. In Lewis lung cancer (LLC1) cells, FPNL containing BLM showed 2.38‐fold and 3.26‐fold higher cytotoxicity compared to PNL‐BLM and free BLM, respectively. Moreover, the uptake of FPNL by these cells was increased as compared to the PNL. Furthermore, FPNL showed significantly higher tumor distribution of BLM in the LLC1 cells and more tumor inhibition efficacy compared to free BLM and PNL. Both formulations of nanoliposomes had longer plasma half‐life than that of free BLM. Therefore, FPNL may be suitable carriers for targeted drug delivery to FR‐positive tumor cells. Abstract : We successfully prepared a novel FR‐targeted liposomal formulation of BLM. This formulation showed higher cytotoxicity and inhibitory effects on xenograft Lewis lung cancer in mouse model. Moreover, this formulation enhanced the survival time of tumor‐bearing mice and efficiently taken up by FR‐positive LLC1 cells. These findings indicate that FPNL‐BLM is a promising formulation for targeted drug delivery to FR‐positive cancer cells.